The Effect of Planting Distance and Spraying with Different Concentrations of (Micronate15) on Vegetative Growth and Yield Traits of Pea Plant (Pisum Sativum L.) - Hassan, Ismael Ahmad (Kurdistan Journal of Applied Research, 2018)
The aim of this study was to find the effect of planting distances and spraying with different concentrations of leaf fertilizer with micronate15 on some vegetative growth traits and yield of pea variety Green Canada in non-heated greenhouses, by using three planting distance (factor A) which includes: A1:20, A2: 30, and A3:40 cm and four spray concentrations as foliar application (factor B) which includes: B0: zero, B1: 0.5, b2: 1.5 and b3: 2.5 liter of water). According to the results of this study the highest plant (124.82cm), number of branches (4.58), fresh weight,(95.94 g) and the total yield (142.41 g)were observed in the distance of planting (30 cm), while the highest value of the pod length was observed from the distance planting in 40 cm which is 8.39 cm. The concentration of 1.5 mL / liter of micronate15 gave the highest values of branches 4.53 branches, fresh weight 97.47 g, number of pods 36.73 pods, number of seeds 8.55 oats, length of the pod 8.83 cm and the total yield 150.78 g. The highest values of the number of branches 5.14 branch, fresh weight 105.72 g, the number of seeds 8.90 seed and the total yield 159.78 g were observed from the interaction between the planting distance of 30 cm and 1.5 mL / liter of nutrient micronate15. Also, the interaction between 20 cm distance and foliar application with 2.5 mL l of micronate15 gave the highest value in the number of leaves which is 53.36.